Analisis Penggunaan Ejaan yang Disempurnakan pada Karangan Teks Pidato Siswa Kelas VIII SMP Negeri 1 Alasa - Pilih Eli Lase; Mastawati Ndruru; Noveri Amal Jaya Harefa; Noibe Halawa (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze the use of the Enhanced Indonesian Spelling System (EYD) in speech texts written by eighth-grade students of SMP Negeri 1 Alasa. The research was inspired by internship findings showing that many students still fail to apply proper spelling rules in formal writing. The study focuses on three main aspects: letter usage, word writing, and punctuation. A qualitative descriptive method was applied. Data were collected from 21 student speeches on the topic “Garbage Problem” through documentation and written tests. The analysis revealed 262 spelling errors, mostly in capital letter usage, followed by word writing and punctuation. The pattern indicates that students have limited understanding of contextual capitalization, correct word formation, and punctuation functions. The study recommends more practical and writing-integrated spelling instruction so that students can produce clearer and more rule-compliant written works in Indonesian.